HOW COST EFFECTIVE IS YOUR V & V?. Issue 1 (6th April 2017) - Pickard, Andrew C.; Nolan, Andy J.
ABSTRACT: There are many reasons for verification and validation (V&V) including their use to mature a product and reduce the overall development costs. However, there are many V&V approaches that can be applied, from review through modeling, analysis and testing. How effective are these at finding issues with the product? How cost effective are they? Does it matter when the approaches are performed, or in what sequence? This paper examines the V&V approaches applied during the development of gas turbine engine control and monitoring systems. How cost effective are they? In some cases, it is a requirement of the certification process that certain verification approaches are used – but if an approach is not cost effective, would you also use it during development of the product?